Potable Water Savings in Multifamily Buildings Using Stormwater Runoff from Impermeable Paved Streets - Thives, Liseane Padilha; Ghisi, Enedir; Mattos da Silva, Natália (European Journal of Sustainable Development, 2018)
Currently, due to the imbalance between demand and supply of water, a short-term possibility of water resources scarcity is a challenge to be faced in several countries. This subject has been a matter of concern for researchers, governments, regulators, and water suppliers. The enforcement of sustainable measures, such as the use of rainwater in buildings, is an alternative to ease the problem; however, the use of stormwater in buildings should also be assessed. The objective of this work is to estimate the potential for potable water savings in multifamily buildings through the use of stormwater runoff collected from paved streets. A case study was carried out, based on actual buildings and catchment areas of urban streets in the city centre of Florianópolis, a city located in southern Brazil. Stormwater runoff is meant to be used for non-potable purposes such as toilet flushing, washing machines, and cleaning. Computer simulations were performed using the Netuno computer programme, version 4. Three scenarios of water consumption were simulated (120, 160 and 200 L/person.day). A paved area equal to 9,058 m² and a rainwater tank capacity of 1,000 m3 were obtained. The potential for potable water savings ranged from 16.91% to 33.39% according to the water demand for non-potable purposes. The use of stormwater runoff harvested from paved streets can be an alternative to save potable water in buildings as well as contribute to a sustainable urban drainage. Keywords: potable water; buildings; stormwater; runoff; paved streets; computer simulation.